Exploration of novel 5′(7′)-substituted-2′- - Do Thi Mai Dung; Phan Thi Phuong Dung; Dao Thi Kim Oanh; Tran Khac Vu; Hyunggu Hahn; Byung Woo Han; Minji Pyo; Young Guk Kim; Sang-Bae Han; Nguyen-Hai Nam (Arabian Journal of Chemistry, 2017)
A series of novel 5′(7′)-substituted-2′-oxospiro[1,3]dioxolane-2,3′-indoline-based N-hydroxypropenamides were designed, synthesized and evaluated for histone deacetylase (HDAC) inhibition and cytotoxicity. It was found that the compounds in this series displayed potent inhibitory effects against HDAC2 with IC50 values as low as 0.284 μM, almost comparable to that of SAHA (IC50, 0.265 μM), a positive control. In Western blot analysis, these compounds also exhibited noted inhibition toward histone deacetylation and this inhibition was found to correlate well with the cytotoxicity of the compounds in three human cancer cell lines. Docking studies indicated the compounds in this series bound to HDAC2 with high binding affinities (∼−9.8 kcal/mol) compared to SAHA (−7.4 kcal/mol).